Holistic Management of Tuberculosis in 49 Years Old Woman with Complex Problems through A Family Medicine Approach : Case Report - Dewantari, Aulia Nissa; Yuniasih, Dewi; Alfiani Laariya, Tira; Nuraga, Hega Fitri; Puspa Sari , Ade (Universitas Ahmad Dahlan, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, transmitted through airborne droplets when an infected person coughs, sneezes, or talks. Environmental conditions, such as poor ventilation and lack of sunlight, can facilitate the persistence of TB bacteria indoors. Sunlight and good air circulation play key roles in reducing bacterial survival. Health cadres are vital in detecting and managing TB cases in their communities. The Sanden Community Health Center runs a TB prevention and control program (P2TB) to help reduce TB incidence. A 49-year-old woman presented with a persistent cough for approximately two months, accompanied by fatigue, significant weight loss, and decreased appetite. The cough was intermittent, sometimes with phlegm, and unresponsive to cough medication. About a month prior, a Rapid Molecular Test (TCM) at a lung hospital in Yogyakarta confirmed TB. She had a history of unhealthy sexual behavior and was previously diagnosed with syphilis but tested negative for HIV. The patient also has metabolic syndrome. On physical examination, she appeared mildly ill but alert (E4M6V5), with a respiratory rate of 16/min. Lung and skin examinations were normal. Abdominal circumference was 112 cm. The patient received education on TB recognition, prevention, and intervention. Interventions were tailored to be patient-centered, family focused, and community-oriented. She was classified as a bacteriologically confirmed TB case, with no previous history of TB treatment and a negative HIV result..